A novel anion doping strategy to enhance upconversion luminescence in NaGd(MoO4)2:Yb3+/Er3+ nanophosphors. Issue 24 (25th May 2017) - Li, Anming; Xu, Dekang; Lin, Hao; Yao, Lu; Yang, Shenghong; Shao, Yuanzhi; Zhang, Yueli; Chen, Zhenqiang
Abstract : A novel and efficient F − anion doping strategy is proposed for enhancing upconversion luminescence in NaGd(MoO4 )2 :Yb 3+ /Er 3+ nanophosphors. Abstract : We propose a novel and efficient F − anion doping strategy for enhancing upconversion luminescence in upconversion nanophosphors. NaGd(MoO4 )2 :Yb 3+ /Er 3+ nanophosphors doped with different F − contents are synthesized hydrothermally. Rietveld refinement results obtained from X-ray diffraction data indicate that the Gd–O bond length decreases and the O–Gd–O bond angle varies with increasing F − content, resulting in augmented local crystal field strength and distorted local site symmetry of the dopant lanthanide sites. Judd–Ofelt analysis suggests that the calculated radiative quantum efficiency of the 4 S3/2 level and the radiative branching ratio of 4 S3/2 → 4 I15/2 transition in F − -doped NaGd(MoO4 )2 :Yb 3+ /Er 3+ nanophosphors are much greater than those in F − anion-free samples. It is inferred that F − anion doping helps to reduce the nonradiative transition probabilities based on the luminescence dynamics. Rietveld refinement results and Judd–Ofelt analysis confirm jointly that doping of interstitial F − anions could enhance local crystal field strength with odd parity and modify site symmetry of the lanthanide activator ions, leading to enhanced radiative transitions and inhibited nonradiative transitions. A maximum of 17-fold enhancement of total emission intensity is found in NaGd(MoO4 )2 :Yb 3+ /Er 3+ /F − nanophosphors compared with F − anion-free counterparts. The proposed F − anion doping strategy provides an alternative approach for enhancing upconversion luminescence efficiency and could be extended to other inorganic upconversion nanomaterials.